Empowering sustainable development: revolutionizing agricultural green total factor productivity through rural digitalization - Zeng, Fanjun; Zhou, Yingying; Wei, Bin (Frontiers in Sustainable Food Systems, 2024)
Introduction The rapid advancement of digital technology has catalyzed the emergence of “digital villages,” presenting both new opportunities and challenges for the digital transformation of agriculture. This transformation has become a core driving force behind sustainable agricultural development. This paper utilizes panel data from 30 provincial-level administrative regions of mainland China (excluding Tibet) for the period 2011 to 2020 to explore how digital rural development (DRD) impacts agricultural green total factor productivity (AGTFP) and examines its underlying mechanisms. Methods Regarding variable measurement, the study employs the entropy weighting method to quantify the DRD and uses an extended Data Envelopment Analysis-Malmquist model to assess AGTFP. For the research approach, the study constructs a two-way fixed effects model to evaluate the impact of DRD on AGTFP and explores the underlying mechanisms. Specifically, the study conducts benchmark regression analysis, endogeneity tests, robustness tests, mechanism examinations, and heterogeneity tests. Results (1) DRD significantly enhances AGTFP, a conclusion that remains robust following the province-year clustering robust standard error estimates, winsorization tests, and excluding COVID-19-affected years. (2) Mechanistic analysis indicates that DRD primarily boosts AGTFP by promoting the development of digital inclusive finance (DIF) and facilitating the integration of primary, secondary, and tertiary industries (IPST). (3) Heterogeneity tests show that the positive impact of DRD on AGTFP is more pronounced in regions with higher levels of informatization and central regions of China. Discussion To harness DRD’s potential more effectively in fostering sustainable agricultural development, policymakers should concentrate on DIF and the IPST. Additionally, the government should pay close attention to disparities in informatization levels and resource allocation across regions and develop targeted strategies accordingly. Fundamentally, this study aims to elucidate China’s efficacy in rural digitalization and the green transformation of agriculture to an international audience. It seeks to provide insights and guidance on formulating more scientific, efficient, and sustainable strategies for agricultural development worldwide, thereby promoting green agricultural growth and supporting rural revitalization.